Pandemic Consumption - Ruediger Bachmann; Christian Bayer; Martin Kornejew (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines how households adjusted their consumption behavior in response to COVID-19 infection risk during the early phase of the pandemic. We use a monthly consumption survey specifically designed by the German Statistical Office covering the second wave of COVID-19 infections from September to November 2020. Households reduced their consumption expenditures on durables and social activities by, respectively, 24 percent and 36 percent in response to one hundred extra infections per one hundred thousand inhabitants per week. The effect was concentrated among the elderly, whose mortality risk from COVID-19 infection was arguably the highest.
Keywords: D12; E21; E32; I12; 330; consumption; health risk; pandemic; COVID-19; survey data